(untitled) (CIPEEX, 2025)
Keywords: Iron deficiency anemia; Iron; Treatment. Bibliographic references: BRITO, M. E. de S. M. e; COSTA, S. de J. .; MENDES, A. L. R.; LIMA , E. M. R. de S. .; SILVA, A. C. R. .; ROCHA, L. R. .; ALVINO, V. de S. .; RODRIGUES, A. E. F. .; SILVA, I. P. . .; LOPES, L. A. de S. .; SILVA, R. C. da .; BARROS, L. de S. R.; SANTANA, L. S. O. S. .; SANTOS , D. O. Fisiopatologia, diagnóstico e tratamento da anemia ferropriva: Uma revisão de literatura. Revista de Casos e Consultoria, [S. l.], v. 12, n. 1, p. e23523, 2021. Disponível em: https://periodicos.ufrn.br/casoseconsultoria/article/view/23523. Teixeira, A. L. G., Morais, M. G., Reis, S. dos, Braga, Y. A. V., Goulart, M. O., amp; Perina, K. C. B.Anemia ferropriva: aspectos clínicos, diagnósticos e terapêuticos. Revista De Medicina, 103(2), e-221582. 2024. Disponível em: https://doi.org/10.11606/issn.1679-9836.v103i2e-221582.Iron deficiency anemia is a widely prevalent hematological condition characterized by iron and hemoglobin (Hb) deficiency in erythrocytes, and is diagnosed when the levels of these components are below the established reference values. Iron, an essential element for the body, is mainly found in hemoglobin, which plays a fundamental role in transporting oxygen to the tissues. Iron is indispensable for the functionality of muscle cells and for the formation of various metabolic enzymes. Iron deficiency anemia manifests itself through symptoms such as weakness, fatigue, hypotension, as well as brittle and rough nails, and is more prevalent in groups that go through periods of high iron demand, such as children, adolescents and pregnant women. This study aimed to analyze prevention strategies and therapeutic approaches for iron deficiency anemia. It is a narrative bibliographic review, carried out in the Scielo and Pubmed databases, including articles published in the years 2019 to 2024 and excluding those that did not meet the theme. It was concluded that iron metabolism is a complex and highly regulated process, which ensures its proper absorption, transportation and storage in the body; in a healthy person, around 10% to 15% of the iron ingested in the diet is absorbed. The iron absorbed in the small intestine, especially in the duodenum, can be stored in ferritin molecules or pass through ferroportin to bind to transferrin, an iron transport protein that takes it to the bone marrow. In the bone marrow, iron is used to form hemoglobin. Preventing iron deficiency anemia therefore depends on a balanced diet, rich in foods such as red meat, beans, lentils, spinach and whole grains, as well as maintaining adequate levels of vitamin C, which enhances iron absorption. The treatment of iron deficiency anemia is based on correcting the iron deficiency, which may involve oral or intravenous supplementation and, in severe cases, blood transfusions. It is also essential to treat the underlying cause if the anemia is secondary to another pathology.